Efektivitas Promosi dengan Media Audiovisual terhadap Penerapan Protokol Kesehatan pada Siswa SD dalam Pencegahan Virus Covid-19 di Era New Normal - Danis Zuliyanto; Roas Irsyada (Indonesian Journal for Physical Education and Sport, 2022)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the acute respiratory syndrome Coronavirus 2 (Sars-CoV-2). During the pandemic, the implementation of health protocols in schools needs special attention from all parties so that the learning process can run optimally. The research used was a quasi-experimental (quasi-experimental) using a one group pretest – posttest design approach with a stratified random sampling technique. Samples were taken from grades 4 to 6 students of SD N Wringinputih 03. Data collection techniques were in the form of tests, observations, and documentation which were then analyzed using the SPSS version 22 program. The results showed that the mean (mean) value of the pre-test was 78.3 which increased to 86.0 on the average score of the post-test. Based on the results of the paired sample t-test (pre-test) and (post-test) it is known that the p value is 0.000 (<0.05). The calculation of the hypothesis shows the value of sig. (2-tailed) of 0.000 < 0.05. Based on these tests, it can be concluded that there are differences in knowledge, attitudes, and practices of implementing health protocols for elementary school students in preventing the spread of the Covid-19 virus in the new normal era before and after health promotion with audio-visual media.